Macrophage development from HSCs requires PU.1-coordinated microRNA expression - Ghani, Saeed; Riemke, Pia; Schönheit, Jörg; Lenze, Dido; Stumm, Jürgen; Hoogenkamp, Maarten; Lagendijk, Anne; Heinz, Sven; Bonifer, Constanze; Bakkers, Jeroen; Abdelilah-Seyfried, Salim; Hummel, Michael; et al. (Blood, 2011)
The differentiation of HSCs into myeloid lineages requires the transcription factor PU.1. Whereas PU.1-dependent induction of myeloid-specific target genes has been intensively studied, negative regulation of stem cell or alternate lineage programs remains incompletely characterized. To test for such negative regulatory events, we searched for PU.1-controlled microRNAs (miRs) by expression profiling using a PU.1-inducible myeloid progenitor cell line model. We provide evidence that PU.1 directly controls expression of at least 4 of these miRs (miR-146a, miR-342, miR-338, and miR-155) through temporally dynamic occupation of binding sites within regulatory chromatin regions adjacent to their genomic coding loci. Ectopic expression of the most robustly induced PU.1 target miR, miR-146a, directed the selective differentiation of HSCs into functional peritoneal macrophages in mouse transplantation assays. In agreement with this observation, disruption of Dicer expression or specific antagonization of miR-146a function inhibited the formation of macrophages during early zebrafish (Danio rerio) development. In the present study, we describe a PU.1-orchestrated miR program that mediates key functions of PU.1 during myeloid differentiation.